KONSEP AJJOARENG-JOA’ DALAM TATANAN SOSIAL MASYARAKAT BUGIS (Perspektif Filsafat Sosial) - Supartiningsih Supartiningsih (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2010)
Bugisnese has a strict and complicated system of social hierarchy. They also have a prestige and a competitive desire to reach a high social status through power, wealth or richness. Their life is based on principles of si pakatau and panngadereng. The principle of si pakatau places a human dignity as a noble creature, and the principle of panngadereng, which is a norm and rule system, regulates social interactions in Bugisnese. Then, those principles manifest in relation between joa’ and joareng that have patron-client mode. The patron-client system is a network of personal relationships that obligates people to one another in a legal fashion. The patron-client relation goes on reciprocal ways in rights and duties. It is a voluntary relation. A patron has duties to protect his joa’ and also concerns to his joa’s prosperities and wealth; a client has duties to serve his patron. Nowadays, the Ajjoreng-Joa’ concept grows with new surrounding conditions and challenges. The concept still lives in their social life but there are value changes and social-cultural developments in its realization. The Ajjoreng-Joa’ concept is a very important factor to get joa’support in political system and it still can be seen in presentpolitical activities.Keywords: ajjoareng-joa’, patron-client, panngandereng, si pakatau.